O ensino e a aprendizagem da polirritmia no violão: uma proposta pedagógica baseada no conceito de dissonância rítmica - Alexandre Gismonti Medeiros Amim (2021)
The present work deals with polyrhythm teaching and learning processes on the guitar and also outside of it. Two paths to describe these processes were considered: a more properly theoretical and a more properly practical path. A genetic relationship between rhythm and meter concepts and those of polyrhythm and polymeter was taken as a starting point and also as an end when discussing the fundamental concepts involved in polyrhythm teaching and learning processes. This relationship was confirmed by the ambiguity of polyrhythm and polymeter words, as they were treated as respectively consequences of rhythm and meter primal words. The concepts of rhythmic dissonance by Yeston (1976) and metric dissonance by Krebs (1989) were considered allusive to polyrhythm, however, the two formers proved to be more specific since they carry different ways of absorbing rhythmic phenomena. While the first former is based on a rational understanding of these phenomena, the second comes more directly from elements that characterize the empirical apprehension of them. Polymeter was not considered to be encompassed by any of these concepts as it implies different metric interpretations of one or more rhythms by different individuals. The scarcity of guitar works which deal with polyrhythm teaching and learning processes was mitigated by the composition of a series of exercises and another series of concert studies which illustrate all together a systematic application of polyrhythms on this instrument. We also carried out an extensive bibliographical review of guitar and body percussion didactic works, from which we listed thirteen (13) polyrhythm teaching procedures which were duly tested during a course we taught to undergraduate students at UFMG. From the results obtained in the course, we reached eleven (11) procedures which, together with the series of exercises and the guitar concert studies, composed our proposal for teaching and learning polyrhythms on the guitar. Finally, we present the fundamental elements of Hessen's theory of knowledge (2000) as particularly appropriate to the theoretical-practical discussions undertaken in our work and that constitute a philosophical outcome for our proposal for teaching and learning polyrhythms on the guitar.